Analyzing Students’ Creative Learning to Improve Speaking Skill Using Technology - Perwitasari, Erma ((JELE) Journal Of English Language and Education, 2022)
The use of CALL in EFL teaching and learning has been widely practiced. Computer technology has been developed in any way to ease learners practice their English skills according to their needs and preferences. This research is a descriptive qualitative that is aimed to know whether EFL students have experience creative learning using computer technology, how the students use computer technology to solve their problems in speaking, and whether using computer technology is suitable for students doing self-directed training. The research data was gathered from students of English-speaking courses in four faculties of Universitas Serang Raya. The findings indicate that students experienced creative learning using computer technology to solve their speaking problems in pronunciation, grammatical word order, and vocabulary. However, students need to be encouraged doing independently extensive speaking practice since they stopped practicing when the courses finished. Teachers’ ability and knowledge using technology to motivate the students to continue creative learning must be further researched.